Polychromatic light excitation and thermal excitation luminous rare earth doped fluorescent powder as well as preparation method and application thereof
By doping different rare earth ions into the Cs2NaLnF6 matrix material and adjusting the trap distribution, multi-color photoexcitation and thermally excited luminescence are achieved, and the problem of difficult real-grabbing and multi-color photoexcitation luminescence in the prior art is solved.
Patent Information
- Application Number
- CN202311166488.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to develop phosphors with deep traps and multi-color light excitation luminescence capabilities, especially in achieving multi-color light excitation luminescence in the same matrix material.
By doping rare earth ions of different concentrations, such as Tb, Dy, Sm, Ho, etc., in the matrix material of Cs2NaLnF6, the trap distribution and luminescence performance of the material are adjusted to achieve multi-color photoexcitation and thermally excited luminescence.
Multicolor light excitation luminescence within the full spectrum range of X-ray excitation is realized, with the luminescence range from 311 nm to 1536 nm, including luminescence in various colors such as ultraviolet, blue, green, yellow, red, near infrared, etc., and thermal excitation luminescence phenomenon occurs after the excitation is stopped.
Smart Images

Figure CN119592328A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent materials, and in particular relates to a rare earth doped fluoride double perovskite multicolor light-excited and thermally-excited luminescent rare earth doped fluorescent powder, and a preparation method and application thereof. Background Art
[0002] Photostimulated luminescence refers to the phenomenon that after the excitation stops, the stored excitation energy is released to emit light under near-infrared light irradiation. Due to the excellent energy storage and controllable release characteristics of photostimulated luminescent materials, they are widely used in biological imaging detection, information storage, encryption and anti-counterfeiting and other fields. Photostimulated luminescent materials are generally composed of a matrix lattice, a luminescent center and a trap capture center. The trap capture center includes an electron or hole capture center. Compared with single luminescent transition metal ions, rare earth ions have the advantages of high color purity, good luminescent stability, and adjustable luminescent range from ultraviolet to near-infrared due to their unique electronic configuration. Therefore, rare earth ions are often used as the luminescent center of photostimulated materials. Unlike the shallow trap capture center of long afterglow materials (below 0.7eV), the captured electrons / holes are spontaneously released from the capture center at room temperature and recombine at the luminescent center to emit light; photostimulated materials require deeper traps, generally above 0.8eV, so that after stopping the light excitation for a long time, the carriers stored in the deep traps can be released under the stimulation of short-wavelength light to achieve photostimulated luminescence. Therefore, for photostimulated materials, the distribution of traps is crucial to their luminescence performance, especially the presence of deep traps. However, deep traps are more difficult to obtain than shallow traps, and the lack of phosphors with suitable deep traps is still a bottleneck in the development of photostimulated luminescent materials.
[0003] Generally, traps come from defects inside the material or defects introduced by doping, so the selection of matrix materials is crucial to the realization of photoluminescence. Compared with traditional oxide phosphors, the radius of fluoride ions in fluorides is smaller, making it easier to achieve ion doping of the material. In addition, fluoride phonon energy is low and the loss is small, making it very suitable as a matrix material for photoluminescence. In particular, potassium cryolite structure materials, also known as double perovskite, have a general structural formula of A2B Ⅰ B ⅢX6 (X=F, Cl, Br, I) has applications in X-ray imaging, lasers, solar cells, lighting, detectors, photocatalysis, etc. Cs2NaLnF6 has low phonon energy and stable chemical and physical properties, and is a good luminescent material that can be used as a matrix. Moreover, both Cs and Ln have strong X-ray absorption capabilities, and their wide band gap and fluorine ion vacancy defects also make Cs2NaLnF6 very suitable for the design of photostimulated luminescence. However, only the monochromatic long afterglow ultraviolet luminescence of Cs2NaYF6 has been developed. The deep trap regulation and photostimulated luminescence of this type of material are still relatively difficult and no one has achieved it. Moreover, due to the difficulty in adjusting the trap distribution and the localization of the luminescence range, it is extremely challenging to achieve multi-color photostimulated luminescence in the same matrix material. Therefore, the development of multi-color photostimulated materials has always been a research difficulty, so that there have been few reports so far. Summary of the invention
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] A rare earth doped phosphor, the phosphor comprising rare earth doped fluoride; the chemical formula of the rare earth doped fluoride is Cs2NaLnF6:xRe 3+ ; Wherein, Ln represents a rare earth element, and Ln is selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, Sc, preferably Gd; Re 3+ represents a doped rare earth ion, Re is selected from one or more (such as two or more) of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc, and Ln and Re 3+ are selected from different rare earth elements; x is the amount of Re doped per mole of rare earth doped fluoride, 0 <x<100mmol%。
[0006] According to an embodiment of the present invention, x is, for example, selected from 0.01 mmol%, 0.05 mmol%, 0.1 mmol%, 0.5 mmol%, 1 mmol%, 5 mmol%, 10 mmol%, 20 mmol%, 30 mmol%, 40 mmol%, 50 mmol%, 60 mmol%, 70 mmol%, 80 mmol%, and 90 mmol%.
[0007] According to an embodiment of the present invention, the rare earth doped fluoride is a double perovskite type.
[0008] According to an embodiment of the present invention, the rare earth-doped fluoride is in the form of micron crystals, for example, a perovskite structure (such as elbainite structure).
[0009] According to a preferred embodiment of the present invention, the rare earth-doped fluoride is Cs2NaGdF6:xRe, x is 0.1mmol%-50mmol%, and x is for example selected from 0.01mmol%, 0.05mmol%, 0.1mmol%, 0.5mmol%, 1mmol%, 5mmol%, 10mmol%, 20mmol%, 30mmol%, 40mmol%, and 50mmol%.
[0010] According to an embodiment of the present invention, the rare earth-doped fluoride realizes multicolor light-stimulated luminescence in the full spectrum range of X-ray excitation in the same matrix material Cs2NaLnF6: after the X-ray stops exciting, the rare earth-doped fluoride can respond in an ultra-wide range of 360 to 980 nm, realize multicolor light-stimulated luminescence of rare earth elements, and emit at least one and two or more of multiple colors such as ultraviolet, blue, green, yellow, red, and near-infrared, and the luminescence band is from 311 nm to 1536 nm. Exemplarily, the rare earth-doped fluoride realizes blue and green light emission by doping Tb; blue light emission by doping Tm; green light emission by doping Ho; yellow light emission by doping Dy; and red light emission by doping Sm. According to an embodiment of the present invention, the rare earth-doped fluoride can realize multicolor thermally stimulated luminescence (luminescence range is 311-1536 nm) in the full spectrum range of X-ray excitation. After the X-ray excitation stops, the rare earth doped fluoride still has the phenomenon of thermally stimulated luminescence, that is, after the X-ray excitation stops, the rare earth doped fluoride is heated to greater than 70°C and above, and the rare earth doped fluoride after X-ray pre-irradiation shows multi-color thermally stimulated luminescence.
[0011] According to an embodiment of the present invention, the rare earth-doped fluoride includes deep traps, and the trap depth of the deep traps is above 0.8eV, preferably 0.8-1.5eV, for example, 0.85eV, 0.89eV, 0.9eV, 0.96eV, 1.0eV, 1.1eV, 1.12eV.
[0012] According to an embodiment of the present invention, after the X-ray excitation stops, the rare earth doped fluoride can also show the multi-color long afterglow luminescence of the rare earth (for example, the luminescence range of the long afterglow luminescence is 311-1536nm). Preferably, the multi-color long afterglow luminescence of the rare earth doped fluoride can be achieved by adjusting the doped rare earth ions. For example, Gd 3+ of 6 P J → 8 S 7 / 2 Emission light at 311nm; Tb 3+ of 5 D3 → 7 F6 emits light at 378nm; Tb3+ of 5 D4→ 7 F5 emits light at 550nm; Tm 3+ of 1 G4→ 3 H6 emits light at 456nm; Ho 3+ of 5 F4→ 5 I8 emits light at 542nm; Dy 3+ of 4 F 9 / 2 → 6 H 13 / 2 Emission light is at 582nm; Sm 3+ of 4 G 5 / 2 → 6 H 7 / 2 Emission light is at 608nm; Pr 3+ of 3 P0→ 3 H6 emits light at 610nm; Yb 3+ of 2 F 5 / 2 → 2 F 7 / 2 Emission light at 990nm; Nd 3+ of 4 F 3 / 2 → 4 I 11 / 2 Emission light at 1058nm; Er 3+ of 4 I 13 / 2 → 4 I 15 / 2 The emission light is at 1536nm.
[0013] According to a preferred embodiment of the present invention, when the rare earth doped fluoride is Cs2NaGdF6:xTb and x is 0.1mmol%-50mmol%, the doping concentration x of Tb is different, and the rare earth doped fluoride Cs2NaGdF6:xTb emits light of different colors after X-ray excitation; preferably, as the doping concentration x of Tb increases, the color-changing light excitation and thermal excitation luminescence of the rare earth doped fluoride Cs2NaGdF6:xTb gradually changes from blue to green after the X-ray excitation stops. Furthermore, when the Tb doping concentration x does not exceed 2.5 mmol%, after X-ray excitation, the photoexcitation and thermal excitation luminescence of the rare earth doped fluoride Cs2NaGdF6:xTb is blue; further, when the Tb doping concentration is above 5 mmol%, after X-ray excitation, the photoexcitation and thermal excitation luminescence of the rare earth doped fluoride Cs2NaGdF6:xTb is green; further, when the Tb doping concentration is between 2.5-5 mmol%, after X-ray excitation, the photoexcitation and thermal excitation luminescence of the rare earth doped fluoride Cs2NaGdF6:xTb is a mixture of green and blue light.
[0014] According to an exemplary embodiment of the present invention, the rare earth-doped fluoride is Cs2NaGdF6:xTb, and x is 0.5mmol% or 30mmol%. Preferably, after the X-ray excitation stops, the rare earth-doped fluoride Cs2NaGdF6:xTb realizes Tb emitting blue light and / or green light. Further, after the X-ray excitation stops, the rare earth-doped fluoride is heated to greater than 70°C and above, and the rare earth-doped fluoride Cs2NaGdF6:xTb after X-ray pre-irradiation realizes Tb emitting blue light and / or green light. Exemplarily, the trap depth of the deep trap of the rare earth-doped fluoride Cs2NaGdF6:xTb is 0.89eV and 1.10eV.
[0015] According to an exemplary embodiment of the present invention, the rare earth doped fluoride is Cs2NaGdF6:xDy, where x is 1.5 mmol%. Preferably, after the X-ray excitation stops, the rare earth doped fluoride Cs2NaGdF6:xDy realizes Dy emission of yellow light. Exemplarily, the trap depth of the deep trap of the rare earth doped fluoride Cs2NaGdF6:xDy is 0.94 eV and 1.12 eV.
[0016] According to an exemplary embodiment of the present invention, the rare earth doped fluoride is, for example, Cs2NaGdF6:xSm, where x is 2.5 mmol%. Preferably, after the X-ray stops exciting, the rare earth doped fluoride Cs2NaGdF6:xSm realizes Sm emitting red light. Exemplarily, the trap depth of the deep trap of the rare earth doped fluoride Cs2NaGdF6:xSm is 0.96 eV.
[0017] According to an exemplary embodiment of the present invention, the rare earth doped fluoride is, for example, Cs2NaGdF6:xHo, where x is 2.5 mmol%. Preferably, after the X-ray stops exciting, the rare earth doped fluoride Cs2NaGdF6:xHo realizes Ho emitting green light. Exemplarily, the trap depth of the deep trap of the rare earth doped fluoride Cs2NaGdF6:xHo is 0.89 eV.
[0018] The present invention also provides a method for preparing the rare earth-doped phosphor. The method is a solid phase reaction method, which specifically comprises the following steps:
[0019] S1. According to the stoichiometric ratio, sodium salt, ammonium salt, cesium salt, rare earth oxide and doped rare earth compound are mixed uniformly to obtain a mixed powder;
[0020] S2, subjecting the mixed powder obtained in step S1 to thermal sintering treatment to obtain sintered powder;
[0021] S3, grinding the sintered powder obtained in step S2, and then performing secondary sintering to obtain the rare earth-doped phosphor.
[0022] According to an embodiment of the present invention, in step S1, the molar ratio of the ammonium salt to the rare earth oxide is (10-12):1.
[0023] According to an embodiment of the present invention, the sodium salt is selected from at least one of sodium bicarbonate, sodium hydroxide, etc., preferably sodium bicarbonate.
[0024] According to an embodiment of the present invention, the ammonium salt is selected from ammonium fluoride.
[0025] According to an embodiment of the present invention, the cesium salt is selected from at least one of cesium carbonate, cesium fluoride, etc., preferably cesium carbonate.
[0026] According to an embodiment of the present invention, the rare earth oxide is selected from oxides containing at least one of the following rare earth elements Ln: La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, Sc. Preferably, the rare earth oxide is selected from La2O3, CeO2, Pr6O 11 , at least one of Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3, Y2O3, and Sc2O3.
[0027] According to an embodiment of the present invention, the doped rare earth compound is selected from compounds (preferably oxides) containing at least one of the doped rare earth elements Re, wherein Re has the meaning as described above, for example, selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, Sc. Preferably, the doped rare earth compound is selected from La2O3, CeO2, Pr6O 11 , at least one or more of Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb4O7, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3, Lu2O3, Y2O3, and Sc2O3.
[0028] According to an embodiment of the present invention, in step S1, the raw materials may be ground after being mixed to make them uniformly mixed. Preferably, the grinding is preferably performed when a solvent is added to the raw materials.
[0029] According to an embodiment of the present invention, in step S1, the solvent is selected from at least one of acetone, ethanol, N,N-dimethylformamide, etc.
[0030] According to an embodiment of the present invention, in step S2, the thermal sintering treatment can be performed using equipment known in the art, such as in a muffle furnace.
[0031] According to an embodiment of the present invention, in step S2, the thermal sintering treatment includes pre-sintering and primary sintering.
[0032] According to an embodiment of the present invention, the pre-sintering includes heating to above 100° C. (eg, 150° C., 200° C.), and sintering for 5 to 8 hours (eg, 6 hours, 7 hours).
[0033] According to an embodiment of the present invention, in step S2, the pre-sintering is performed in an air atmosphere.
[0034] According to an embodiment of the present invention, the primary sintering includes sintering at a temperature above 400° C. (eg, 450° C., 500° C.) for 20 to 40 minutes (eg, 30 minutes).
[0035] According to an embodiment of the present invention, in step S3, the secondary sintering can be performed using equipment known in the art, such as in a tube furnace.
[0036] According to an embodiment of the present invention, in step S3, the secondary sintering is performed under the protection of an inert gas.
[0037] According to an embodiment of the present invention, in step S3, the secondary sintering includes: a sintering temperature of 600-750° C. (eg, 650° C., 700° C.), and a reaction time of 9-12 hours (eg, 10 hours, 11 hours).
[0038] The present invention also provides application of the rare earth doped fluorescent powder, for example, application in preparing composite materials.
[0039] The present invention also provides a composite material, which comprises the rare earth-doped fluorescent powder.
[0040] According to an embodiment of the present invention, the composite material includes a matrix and the rare earth-doped phosphor.
[0041] According to an embodiment of the present invention, the substrate is selected from at least one of polydimethylsiloxane (PDMS), transparent silicone resin, thermoplastic polyurethane rubber (TPU) and the like.
[0042] According to an embodiment of the present invention, in the composite material, the mass ratio of the rare earth doped phosphor to the matrix is 1:(8-50), preferably 1:(10-30), and exemplarily 1:10, 1:20, and 1:30.
[0043] According to an embodiment of the present invention, the composite material is preferably a film structure.
[0044] According to an embodiment of the present invention, the film thickness of the composite material is 0.01-10 mm, preferably 0.1-1 mm, for example, 0.5 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm.
[0045] According to an embodiment of the present invention, the composite material further comprises an additive. Preferably, the additive can be selected from additives known in the art, such as tin dioxide (SnO2). Preferably, the additive can be selected according to the properties of the composite material; for example, in order to increase the opacity of the composite material, the additive is selected from tin dioxide (SnO2).
[0046] According to an embodiment of the present invention, in the composite material, the mass ratio of the additive to the rare earth-doped phosphor is 1:(3-30), preferably 1:(5-20), for example, 1:10, 1:15, 1:20, 1:25.
[0047] The present invention also provides a method for preparing the composite material, the method comprising the following steps:
[0048] (1) collecting the rare earth-doped phosphor;
[0049] (2) then mixing the rare earth-doped phosphor of step (1) and the matrix to obtain a mixture;
[0050] (3) The mixture is subjected to light aging to form a composite thin film material.
[0051] According to an embodiment of the present invention, in step (1), the collecting means sieving the phosphor. Preferably, a sieve of 300 mesh or less is used for sieving, preferably 150 mesh.
[0052] According to an embodiment of the present invention, in step (2), the mass ratio of the rare earth doped phosphor to the matrix is 1:(8-50), preferably 1:(10-30), and exemplarily 1:10, 1:20, and 1:30.
[0053] According to an embodiment of the present invention, in step (2), an additive may be added to the mixture, and the additive has the meaning as described above. Further, the mass ratio of the additive to the rare earth-doped phosphor is 1:(3-30), preferably 1:(5-20).
[0054] According to an embodiment of the present invention, in step (2), the mixture can also be prepared into a desired shape by methods known in the art; for example, in order to obtain a thin film, the mixture can be spin-coated onto a quartz plate.
[0055] In step S3, the spin coating speed is 600-1000 rpm, and the spin coating time is 5-10 s.
[0056] In step (3), the light aging condition is: irradiation under UV light for a period of time, such as 5-30 minutes, and for example 10 minutes, 20 minutes. Preferably, the UV light can be a UV light source known in the art, which is not specifically limited in the present invention.
[0057] The present invention also provides applications of the rare earth doped fluorescent powder and / or composite material, such as applications in the fields of detection devices, information storage, encryption and anti-counterfeiting.
[0058] Beneficial effects of the present invention:
[0059] 1) The present invention synthesizes a series of Cs2NaLnF6 fluoride double perovskite structural materials with different rare earth doping and high stability by a high temperature solid phase method. The synthesis conditions are easy to control, the preparation method is simple, easy to operate, and has good repeatability. The Cs2NaLnF6 material prepared by the method of the present invention has high stability and good luminescence performance.
[0060] 2) The present invention provides for the first time a luminescence control strategy for multicolor light excitation and thermal excitation of rare earth-doped Cs2NaLnF6, which has potential value for the design, development and promotion of this type of luminescent materials.
[0061] 3) The present invention takes advantage of the wider band gap and suitable fluorine vacancy traps of Cs2NaLnF6 material, and can effectively regulate the trap distribution and luminescence performance of the material by doping with different concentrations and types of rare earth ions, thereby achieving multicolor light excitation and thermal excitation luminescence of one or more rare earth ions at different doping concentrations, and has high application potential.
[0062] 4) The Cs2NaLnF6 phosphor composite film material of the present invention has excellent flexibility, good water resistance, high stability, and a simple preparation process, and has great application prospects in the fields of information storage and encryption anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 Schematic diagram of the photoexcitation luminescence mechanism of Tb ions after stopping X-ray excitation of the Cs2NaGdF6:Tb phosphor obtained in Example 1;
[0064] Figure 2 is the X-ray powder diffraction pattern of the Cs2NaGdF6:Tb phosphor obtained in Example 1;
[0065] Figure 3 The light-stimulated luminescence spectra of the Cs2NaGdF6:Tb phosphor obtained in Example 1 with different doping concentrations of Tb ions (0.5 mmol% and 30 mmol%) after stopping X-ray excitation;
[0066] Figure 4 The thermograms of the Cs2NaGdF6:Tb phosphor obtained in Example 1 with different doping concentrations of Tb ions (0.5mmol% / 30mmol%) after stopping X-ray excitation;
[0067] Figure 5 The light-stimulated luminescence spectra of the Cs2NaGdF6:30mmol%Tb phosphor obtained in Example 1 at different times after stopping the X-ray excitation;
[0068] Figure 6 This is a comparison diagram of the light-stimulated luminescence of the Cs2NaGdF6:30mmol%Tb phosphor obtained in Example 1 after stopping the X-ray excitation under light stimulation of different wavelengths;
[0069] Figure 7 This is a photo-stimulated luminescence spectrum of Dy ions in the Cs2NaGdF6:1.5mmol%Dy phosphor obtained in Example 2 after stopping X-ray excitation;
[0070] Figure 8 This is the thermal emission spectrum of the Cs2NaGdF6:1.5mmol%Dy phosphor obtained in Example 2 after stopping the X-ray excitation;
[0071] Fig. 9 This is a photo-stimulated luminescence spectrum of Sm ions of the Cs2NaGdF6:2.5mmol%Sm phosphor obtained in Example 3 after stopping X-ray excitation;
[0072] Fig.10 This is the thermal emission spectrum of the Cs2NaGdF6:2.5mmol%Sm phosphor obtained in Example 3 after stopping the X-ray excitation;
[0073] Fig.11 This is the photo-stimulated luminescence spectrum of Ho ions in the Cs2NaGdF6:2.5mmol%Ho phosphor obtained in Example 4 after stopping X-ray excitation.
[0074] Fig.12 This is the thermal emission spectrum of the Cs2NaGdF6:2.5mmol%Ho phosphor obtained in Example 4 after stopping the X-ray excitation;
[0075] Fig.13 The present invention is a schematic diagram of the process of synthesizing Cs2NaLnF6 phosphor composite thin film material.
[0076] Fig.14 This is a real picture of the thermally stimulated luminescence of the Cs2NaGdF6:Tb phosphor composite thin film material obtained in Example 6. DETAILED DESCRIPTION
[0077] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0078] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0079] The instruments used in the present invention are as follows: X-ray powder diffraction for testing nanocrystals (the instrument model is MiniFlex2, the manufacturer is Rigaku, and the copper target radiation wavelength is λ=0.154187nm), X-ray light source (the instrument model is Mini-X2, the manufacturer is Amptek), and light-stimulated luminescence spectrum (the instrument model is FLS980, the manufacturer is Edinburgh, and the stimulating excitation light source is a 980nm laser and an OPO laser).
[0080] Example 1
[0081] Preparation of Cs2NaGdF6:xTb (x = 0.5 mmol% or (x = 30 mmol%) phosphor:
[0082] (1) Uniform mixing of raw material powders: 4.975 mmol of gadolinium oxide (Gd2O3), 0.025 mmol of terbium oxide (Tb4O7), 5 mmol of sodium bicarbonate, 5 mL of cesium carbonate, and 50 mL of ammonium fluoride were weighed into a mortar, and 3 ml of acetone was added to mix, and the mixture was fully ground to obtain a raw material of Cs2NaGdF6:xTb (x = 0.5 mmol%);
[0083] Weigh 3.5 mmol of gadolinium oxide (Gd2O3), 1.5 mmol of terbium oxide (Tb4O7), 5 mmol of sodium bicarbonate, 5 mL of cesium carbonate, and 50 mL of ammonium fluoride in a mortar, add 3 ml of acetone, mix, and grind thoroughly to obtain the raw material of Cs2NaGdF6:xTb (x=30 mmol%).
[0084] The raw materials of step (1) are respectively subjected to the following steps:
[0085] (2) Sintering heat treatment: The mixed powders obtained in step (1) were subjected to sintering heat treatment using a muffle furnace, heated to 150°C, and pre-sintered for 7 hours; the heating was performed in an air atmosphere. To promote the formation of the phosphor, the pre-sintering was further sintered at 450°C for 30 minutes to obtain a sintered powder.
[0086] (3) Secondary sintering heat treatment: The sintered powder obtained in step (2) is ground again and further sintered in a tubular furnace. The heating reaction during the secondary sintering is carried out under the protection of an inert gas. The sintering temperature is 700°C and the reaction time is 10 hours to prepare the product Cs2NaGdF6:xTb (x=0.5mmol%) and Cs2NaGdF6:xTb (30mmol%) phosphors.
[0087] (4) Sieving and collecting the rare earth fluoride potassium cryolite structure phosphor: Grind the product obtained in step (3) into fine powder and sieve it for later use.
[0088] Figure 1 Schematic diagram of the photo-stimulated luminescence mechanism of Tb ions after the X-ray excitation of the Cs2NaGdF6:Tb phosphor obtained in this example is stopped. Figure 2 is the X-ray powder diffraction pattern of the Cs2NaGdF6:Tb phosphor obtained in this example; Figure 3 The light-stimulated luminescence spectra of the Cs2NaGdF6:Tb phosphor obtained in this embodiment with different doping concentrations of Tb ions after stopping X-ray excitation are shown in FIG. Figure 3 1 is Tb doping concentration of 0.5mmol%, and the monitored wavelength is Tb at 378nm 3+ of 5 D3 → 7F6 blue light emission, Figure 3 2 is Tb doping concentration of 30mmol%, and the Tb under the monitoring wavelength of 550nm 3+ of 5 D4→ 7 F5 green light emission. Figure 3 It can be seen that after stopping the X-ray excitation, the luminescence intensity under the 980nm irradiation stimulation is significantly increased, that is, it is light-stimulated luminescence. It can be seen that the present invention realizes blue and / or green light-stimulated luminescence of Cs2NaGdF6 phosphor by doping different concentrations of Tb.
[0089] Figure 4 The thermal emission spectra of the Cs2NaGdF6:Tb phosphor obtained in this embodiment with different doping concentrations of Tb ions (x=0.5mmol% and x=30mmol%) after stopping X-ray excitation are the characterization of the trap depth. The higher the peak temperature, the deeper the trap depth. Figure 4 1 represents the curve when the Tb doping concentration x is 0.5 mmol%, and 2 represents the curve when the Tb doping concentration x is 30 mmol%. Figure 4 It can be seen that the trap depths of the Cs2NaGdF6:Tb phosphor are different for different doping concentrations of Tb. For example, when x is 0.5 mmol%, the trap depths are 0.70 eV, 0.89 eV, and 1.10 eV. When x is 30 mmol%, the trap depths are 0.71 eV, 0.89 eV, and 1.11 eV. It can be seen that the Cs2NaGdF6:Tb phosphor prepared in this embodiment has deep traps.
[0090] The photoluminescence spectra of Cs2NaGdF6:30mmol%Tb phosphor were tested at different times after stopping X-ray excitation. The results are as follows Figure 5 As shown. Figure 5 It can be seen that 150 hours after the X-rays were stopped, the Cs2NaGdF6:30mmol%Tb phosphor still exhibited stable photoexcited luminescence, indicating that the Cs2NaGdF6:Tb phosphor has a strong energy storage capacity.
[0091] After stopping the X-ray excitation, light sources of different wavelengths were used to stimulate the pre-irradiated Cs2NaGdF6:30mmol%Tb phosphor and its luminescence intensity was tested. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the Cs2NaGdF6:Tb phosphor responds to light stimulation in the range of 360nm to 980nm.
[0092] Example 2
[0093] Preparation of Cs2NaGdF6:1.5mmol%Dy phosphor:
[0094] (1) Uniform mixing of raw material powders: 4.925 mmol of gadolinium oxide (Gd2O3), 0.075 mmol of dysprosium oxide (Dy2O3), 5 mmol of sodium bicarbonate, 5 mL of cesium carbonate, and 50 mL of ammonium fluoride were weighed into a mortar, and 3 ml of acetone was added to mix and the mixture was thoroughly ground.
[0095] (2) Sintering heat treatment: The mixed powder obtained in step (1) is heat treated in a muffle furnace, heated to 150°C, and pre-sintered for 7 hours; the heating is performed in an air atmosphere. To promote the formation of the phosphor, the pre-sintering is further sintered at 450°C for 30 minutes to obtain a sintered powder.
[0096] (3) Secondary sintering heat treatment: The sintered powder obtained in step (2) is ground again and further sintered in a tubular furnace. The heating reaction during the secondary sintering is carried out under the protection of an inert gas. The sintering temperature is 700° C. and the reaction time is 10 hours to obtain the product Cs2NaGdF6:1.5mmol%Dy phosphor.
[0097] (4) Sieving and collecting the rare earth fluoride potassium cryolite structure phosphor: The product obtained in step (3) is ground into fine powder and sieved for later use.
[0098] Figure 7 The photoluminescence spectra of the Cs2NaGdF6:1.5mmol%Dy phosphor obtained in this example with different doping concentrations of Dy ions after stopping X-ray excitation are shown in Figure 1. 3+ of 4 F 9 / 2 → 6 H 13 / 2 Yellow emission, yellow light-stimulated luminescence of Cs2NaGdF6 phosphor is achieved by doping Dy. Figure 8 This is the thermal emission spectrum of the Cs2NaGdF6:1.5mmol%Dy phosphor obtained in this example after stopping the X-ray excitation. The trap depths of the phosphor are 0.70eV, 0.94eV, and 1.12eV, indicating that the Cs2NaGdF6:1.5mmol%Dy phosphor prepared in this example has deep traps.
[0099] Example 3
[0100] Preparation of Cs2NaGdF6:2.5mmol%Sm phosphor:
[0101] (1) Uniform mixing of raw material powders: 4.825 mmol of gadolinium oxide (Gd2O3), 0.125 mmol of samarium oxide (Sm2O3), 5 mmol of sodium bicarbonate, 5 mL of cesium carbonate, and 50 mL of ammonium fluoride were weighed into a mortar, and 3 ml of acetone was added to mix and the mixture was thoroughly ground.
[0102] (2) Sintering heat treatment: The mixed powder obtained in step (1) is heat treated in a muffle furnace, heated to 150°C, and pre-sintered for 7 hours; the heating is performed in an air atmosphere. To promote the formation of the phosphor, the pre-sintering is further sintered at 450°C for 30 minutes to obtain a sintered powder.
[0103] (3) Secondary sintering heat treatment: The sintered powder obtained in step (2) is ground again and further sintered in a tubular furnace. The heating reaction is carried out under the protection of an inert gas. The sintering temperature is 700° C. and the reaction time is 10 hours to obtain the product Cs2NaGdF6:2.5mmol%Sm phosphor.
[0104] (4) Sieving and collecting the rare earth fluoride potassium cryolite structure phosphor: Grind the product obtained in step (3) into fine powder and sieve it for later use.
[0105] Fig. 9 The photoluminescence spectra of the Cs2NaGdF6:2.5mmol%Sm phosphor obtained in this example with different doping concentrations of Sm ions after stopping X-ray excitation are shown in Figure 2. 3+ of 4 G 5 / 2 → 6 H 7 / 2 Red emission, and pink light-stimulated luminescence of Cs2NaGdF6 fluorescence is achieved by doping Sm. Fig.10 This is the thermal emission spectrum of the Cs2NaGdF6:2.5mmol%Sm phosphor obtained in this example after stopping the X-ray excitation. The trap depth of the phosphor is 0.96eV, indicating that the Cs2NaGdF6:2.5mmol%Sm phosphor prepared in this example has deep traps.
[0106] Example 4
[0107] Preparation of Cs2NaGdF6:2.5mmol%Ho phosphor:
[0108] (1) Uniform mixing of raw material powders: 4.825 mmol of gadolinium oxide (Gd2O3), 0.125 mmol of holmium oxide (Ho2O3), 5 mmol of sodium bicarbonate, 5 mL of cesium carbonate, and 50 mL of ammonium fluoride were weighed into a mortar, and 3 ml of acetone was added to mix and the mixture was thoroughly ground.
[0109] (2) Sintering heat treatment: The mixed powder obtained in step (1) is heat treated in a muffle furnace, heated to 150°C, and pre-sintered for 7 hours; the heating is carried out in an air atmosphere. In order to promote the formation of the phosphor, the pre-sintering is further sintered at 450°C for 30 minutes to obtain a sintered powder. (3) Secondary sintering heat treatment: The sintered powder obtained in step (2) is ground again, and further sintered in a tubular furnace for a secondary sintering. During the secondary sintering, the heating reaction is carried out under the protection of an inert gas, the sintering temperature is 700°C, and the reaction time is 10 hours, to prepare the product Cs2NaGdF6:2.5mmol%Ho phosphor.
[0110] (4) Sieving and collecting the rare earth fluoride potassium cryolite structure phosphor: The product obtained in step (3) is ground into fine powder and sieved for later use.
[0111] Fig.11 The photoluminescence spectra of the Cs2NaGdF6:2.5mmol%Ho phosphor obtained in this example with different doping concentrations of Ho ions after stopping X-ray excitation are shown in Figure 2. The Ho 3+ of 5 F4→ 5 I8 green emission, green photoexcited luminescence of Cs2NaGdF6 phosphor is achieved by doping Ho. Fig.12 This is the thermal emission spectrum of the Cs2NaGdF6:2.5mmol%Ho phosphor obtained in this example after stopping the X-ray excitation. The trap depths of the phosphor are 0.70eV and 0.89eV, indicating that the Cs2NaGdF6:2.5mmol%Ho phosphor prepared in this example has deep traps.
[0112] Example 5
[0113] Preparation of Cs2NaGdF6:0.5mmol%Tb composite thin film material:
[0114] (1) Uniform mixing of raw material powders: 4.975 mmol of gadolinium oxide (Gd2O3), 0.025 mmol of terbium oxide (Tb4O7), 5 mmol of sodium bicarbonate, 5 mL of cesium carbonate, and 50 mL of ammonium fluoride were weighed into a mortar, and 3 ml of acetone was added to mix and the mixture was thoroughly ground.
[0115] (2) Sintering heat treatment: The mixed powder obtained in step (1) is heat treated in a muffle furnace, heated to 150°C, and pre-sintered for 5 to 8 hours; the heating is performed in an air atmosphere. To promote the formation of the phosphor, the pre-sintering is further sintered at 450°C for 20 to 40 minutes to obtain a sintered powder.
[0116] (3) Secondary sintering heat treatment: The sintered powder obtained in step (2) is ground again and further sintered in a tubular furnace. The heating reaction during the secondary sintering is carried out under the protection of an inert gas. The sintering temperature is 600 to 750° C. and the reaction time is 9 to 12 hours to obtain the product Cs2NaGdF6:0.5mmol%Tb phosphor.
[0117] (4) Sieving and collecting the rare earth fluoride potassium cryolite structure phosphor: The product obtained in step (3) is ground into fine powder and sieved for later use.
[0118] (5) Preparation of composite film materials: Fig.13 The process schematic diagram shows that the rare earth-doped Cs2NaGdF6:0.5mmol% Tb phosphor collected through a sieve in step (4) is evenly mixed with tin dioxide (SnO2) and a matrix polydimethylsiloxane (PDMS) in a mass ratio of 1.2:0.2:12, and spin-coated onto a quartz plate at 800rpm for 5s; UV irradiation is performed for 5min to form a 0.5mm composite thin film material.
[0119] Fig.14 This is a picture of the thermally stimulated luminescence of the composite thin film material obtained in this embodiment after being heated to 100°C three hours after the X-ray excitation is stopped. It can be seen that the composite thin film material of this embodiment after irradiation can emit blue visible light through thermally stimulated luminescence, and the trap depths of the phosphor are 0.70eV, 0.89eV, and 1.10eV.
[0120] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A rare earth doped phosphor, characterized in that: The phosphor comprises rare earth doped fluoride; the chemical formula of the rare earth doped fluoride is Cs2NaLnF6:xRe 3+ ; Wherein, Ln represents a rare earth element, and Ln is selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, Sc; Re 3+ represents a doped rare earth ion, Re is selected from one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Sc, and Ln and Re 3+ are selected from different rare earth elements; x is the amount of Re doped per mole of rare earth doped fluoride, 0 <x<100mmol%。 2. The rare earth doped phosphor according to claim 1, characterized in that: The rare earth doped fluoride is of double perovskite type. Preferably, the rare earth-doped fluoride is in the form of micron crystals. Preferably, the rare earth doped fluoride is Cs2NaGdF6:xRe, where x is 0.1 mmol%-50 mmol%.
3. The rare earth doped phosphor according to claim 1 or 2, characterized in that: The rare earth-doped fluoride realizes multicolor light-stimulated luminescence in the full spectrum range of X-ray excitation in the same matrix material Cs2NaLnF6: after the X-ray excitation stops, the rare earth-doped fluoride can respond in an ultra-wide range of 360 to 980 nm, realizing multicolor light-stimulated luminescence of rare earth elements, emitting at least one and two or more lights in multiple colors such as ultraviolet, blue, green, yellow, red, and near-infrared, and the luminescence band is from 311 nm to 1536 nm. Preferably, the rare earth-doped fluoride includes deep traps, and the trap depth of the deep traps is above 0.8 eV. Preferably, after the X-ray excitation stops, the rare earth-doped fluoride exhibits multi-color thermally stimulated luminescence of the rare earth. Preferably, after the X-ray excitation stops, the rare earth-doped fluoride can still exhibit multi-color long afterglow luminescence of the rare earth. Preferably, when the rare earth-doped fluoride is Cs2NaGdF6:xTb and x is 0.1mmol%-50mmol%, the doping concentration x of Tb is different, and the rare earth-doped fluoride Cs2NaGdF6:xTb emits light of different colors after X-ray excitation; preferably, as the doping concentration x of Tb increases, the color-changing light excitation and thermal excitation luminescence of the rare earth-doped fluoride Cs2NaGdF6:xTb changes from blue to green after the X-ray excitation stops.
4. The method for preparing the rare earth doped phosphor according to any one of claims 1 to 3, characterized in that: The preparation method is a solid phase reaction method, which specifically comprises the following steps: S1. According to the stoichiometric ratio, the sodium salt, the ammonium salt, the cesium salt, the rare earth oxide and the doped rare earth compound are uniformly mixed to obtain a mixed powder; S2, subjecting the mixed powder obtained in step S1 to thermal sintering treatment to obtain sintered powder; S3, grinding the sintered powder obtained in step S2, and then performing secondary sintering to obtain the rare earth-doped phosphor.
5. The preparation method according to claim 4, characterized in that: In step S1, the molar ratio of the ammonium salt to the rare earth oxide is (10-12):
1. Preferably, the sodium salt is selected from at least one of sodium bicarbonate and sodium hydroxide. Preferably, the ammonium salt is selected from ammonium fluoride. Preferably, the cesium salt is selected from at least one of cesium carbonate and cesium fluoride. Preferably, the rare earth oxide is selected from oxides containing at least one of the following rare earth elements Ln: La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, Sc. Preferably, the doped rare earth compound is selected from compounds containing at least one of the doped rare earth elements Re.
6. The preparation method according to claim 4 or 5, characterized in that: In step S2, the thermal sintering process includes pre-sintering and primary sintering. Preferably, the pre-sintering includes heating to above 100° C. and sintering for 5 to 8 hours. Preferably, in step S2, the pre-sintering is performed in an air atmosphere. Preferably, the primary sintering includes sintering at a temperature above 400° C. for 20 to 40 minutes. Preferably, in step S3, the secondary sintering is performed under the protection of an inert gas. Preferably, in step S3, the secondary sintering includes: a sintering temperature of 600-750° C., and a reaction time of 9-12 hours.
7. Use of the rare earth doped phosphor according to any one of claims 1 to 3, characterized in that: It is used to prepare composite materials.
8. A composite material, comprising the rare earth-doped phosphor according to any one of claims 1 to 3. Preferably, the composite material comprises a matrix and the rare earth-doped phosphor. Preferably, the matrix is selected from at least one of polydimethylsiloxane, transparent silicone resin, and thermoplastic polyurethane rubber. Preferably, in the composite material, the mass ratio of the rare earth doped phosphor to the matrix is 1:(8-50). Preferably, the composite material is a film structure. Preferably, the film thickness of the composite material is 0.01-10 mm.
9. The method for preparing the composite material according to claim 8, characterized in that: The preparation method comprises the following steps: (1) collecting the rare earth-doped phosphor according to any one of claims 1 to 3; (2) then mixing the rare earth-doped phosphor of step (1) and the matrix to obtain a mixture; (3) The mixture is subjected to light aging to form a composite thin film material.
10. Use of the rare earth doped phosphor according to any one of claims 1 to 3 and / or the composite material according to claim 8 in the fields of detection devices, information storage, encryption and anti-counterfeiting.
Citation Information
Cited By
Rare earth doped luminescent material and preparation method and application thereof
CN121914728A
A rare earth doped luminescent material, a method for preparing the same and use thereof
CN121914728B